PEMIKIRAN IKHWANUS SHAFA TENTANG PENDIDIKAN DAN RELEVANSINYA DENGAN ERA GLOBALISASI - Anwar, Khaerul (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2019)
The world of education, especially in Indonesia, is still faced with various problems. This situation is very visible, began to shift the educational orientation of the students who tend to make education only as a